Observation of local cardiac electrophysiological changes during off-pump coronary artery bypass grafting using epicardial mapping. (March 2019) - Li, Qin; Li, Haiming; Wang, Liangshan; Liu, Changcheng; Li, Songnan; Chen, Yingwei; Zhang, Yafei; Gu, Chengxiong
Objectives: At present, there is no effective method of evaluating the electrophysiological changes in cardiac myocytes during off-pump coronary artery bypass grafting (OPCAB). Therefore, we preliminarily explored the relationship between electrophysiological characteristics and the changes in cardiac function of 24 patients undergoing OPCAB. Methods: We used the CARTO3 system for epicardial electrophysiological mapping before surgery, during left anterior descending branch anastomosis, diagonal branch anastomosis and after surgery for 24 patients undergoing OPCAB. Data, including local activation time (LAT), bipolar voltage value (BV) and conduction velocity, were processed and analyzed by the system. Intraoperative invasive blood pressure, heart rate and arterial blood gas analysis data were recorded. Continuous electrocardiography (ECG) monitoring was performed three days after surgery. Routine resting myocardial perfusion imaging (MPI) and adenosine stress-gated MPI were performed before surgery. Patients were re-examined before discharge. Results: By analyzing the change in the LAT value, we found that the order of excitation of local myocardial cells changed after surgery. In addition, the LAT change in myocardial cells closer to the anastomosis was more significant. The earliest pacing point on the left anterior descending (LAD) coronary artery territory map was the third point (from the proximal to distal LAD) before OPCAB, but the earliest pacing point moved down to the fourth point (closer to the anastomosis) after the diagonal (DIA) anastomosis was complete. On the DIA territory map, the earliest pacing point was the fourth point before OPCAB; this moved up to the third point (closer to the anastomosis) after DIA bypass grafting. The voltages of all points were increased after myocardial revascularization. Compared with the preoperative period, the third, fourth and fifth points on the LAD territory map increased significantly after LAD anastomosis was complete (p=0.007, p=0.001, p=0.009, respectively). On the DIA territory map, the voltages of the first, second and third points were remarkably increased after completing the DIA anastomosis compared to before OPCAB and after LAD anastomosis completion (p=0.001, p=0.008, p<0.001 and p=0.006, p=0.032, p=0.002, respectively). The average conduction velocity (ACV) of all mapped points increased after OPCAB compared with before OPCAB (p<0.05). Postoperative resting MPI and adenosine stress-gated MPI showed that left ventricular global systolic function improved, the left ventricular ejection fraction (LVEF) increased significantly (p<0.05) and the left ventricular end systolic volume (LVESV) decreased significantly (p<0.05) compared to the preoperative MPI. Conclusions: Adequate surgical coronary revascularization could lead to more stable electrical activity of local cardiomyocytes, thus, illustrating the specific mechanism of coronary revascularization for improving the cardiac function from an electrophysiological perspective.